Increasing student engagement and retention using online learning activities wikis, blogs and webquests - Wankel, Laura A.; Blessinger, Patrick (Bingley, U.K. : Emerald, 2012)
Increasing Student Engagement and Retention using Social Technologies: Facebook, e-portfolios and other Social Networking Services uses case studies, surveys, and literature reviews to examine how these social media technologies are being used to improve writing and publishing skills in students, create engaging communities of practice, and how these tools are being used for e-Mentoring and constructing online reputations. Chapters include applying positive psychology and cognitive styles in user design, designing outcome based curricula using student personality types, engaging second language students through electronic writing tasks, applying psychological variables on the academic use of social media, using social media to motivate students to take charge of their own learning processes, and creatively using technology to enhance teacher education. This volume will also discuss a framework for deploying and assessing these technologies in higher education institutions.
New vistas in higher education : an introduction to using social technologies / Laura A. Wankel, Patrick Blessinger -- Holistic learner engagement for success in the innovation age : portfolio, strengths-based, and collaborative learning strategies / Amy K. Scatliff, Andrea Meier -- How social media enhanced learning platforms challenge and motivate students to take charge of their own learning processes / Lisbet Pals Svendsen -- Engaging second/foreign language students through electronic writing tasks : when learning design matters / Catherine G. Caws -- Influence of psychological variables on the academic use of Facebook / Luís Simões, Luís Borges Gouveia -- Designing outcome-based curriculum for industry-relevant courses in engineering education : integrating social networking, information and communication technology, modified Bloom's taxonomy, and student personality types / Satyadhyan Chickerur, Aswatha Kumar M -- Computer-aided learning and task-based learning : engaging learners in contextualizing grammar / Jessie Grace U. Rubrico -- Technology approaches to final papers and projects / Nathan E. Whitley-Grassi, Patricia Hoefler -- Using technology to enhance teacher education / Barbara Schwartz-Bechet, Eva Garin -- Going beyond the traditional essay : how new technologies are transforming student engagement with writing outcomes / Michael Truong, Anne Zanzucchi.
Includes index.
Print version record
Keywords: Education -- Computers & Technology; Education -- Distance Education & Learning; Teachers' classroom resources & material; Educational: IT & computing, ICT; Internet in higher education; Online social networks